(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this paper we will explain the detail regarding business concept of electronic commerce. E-commerce is the exchange of money for goods or services between companies and end consumers. The most common definition of ecommerce is that of a web based catalogue from which buyers can order products and sellers can receive payments. Ecommerce has two broader forms .i.e. Business to Business and Business to Consumer. The main idea behind business-to-business (B2B) is to handle sale and purchase of goods and services between businesses, such as between a manufacturer and a wholesaler, or between a wholesaler and a retailer. Business to Consumer (B2C) ecommerce caters businesses with the system that permit them to deliver buyers to the merchants and gain from the commission rewards provided by the merchants.